The Role of Geography Learning in Developing Conservation Character of Participant in SMA Negeri 9 Gowa - Syarif, Erman - (UNM Geographic Journal, 2018)
Environmental degradation that occurs in Indonesia increases dramatically lately even though there have been so many efforts to deal with. One of the conservation efforts that can be carried out is through formal education especially in geographic learning process. This study aims 1) to identify characteristic values and conservation behavior of learners, 2) to identify the obstacles and solutions in integrating characteristic values and conservation behavior in geographic learning process. This research is qualitative which employs purposive sampling method to maintain the samples meanwhile data analysis consists of data collection, data reduction, data presentation and conclusion. The results show that: 1) the characteristic values that can be integrated in the learning process consist of discipline, responsibility, environmental responsibility, honesty and creativity. 2) the obstacles in integrating characteristic values and conservation behaviors such as teachers have difficulties in delivering materials, lack of role model and the attitude and sympathy of learners to environment are less due to lack of support from parents and community. 3) solution to integrate characteristic values and conservation behaviors in geographic learning process is the head master and top management are supposed to give role model and invite the speaker or expert as well as socialization to community. Additionally, some advices might be provided consisted of 1) for teaches, they should be able to build the learner’s perspective toward conservation behavior. 2) for learners, they shall be more active, motivated and creative in learning.